PENGEMBANGAN MEDIA PEMBELAJARAN MENGGUNAKAN APLIKASI PREZI SEBAGAI MEDIA PRESENTASI DENGAN PENDEKATAN ELABORASI PADA MATERI SISTEM PERNAPASAN MANUSIA DI KELAS XI SMA - Asma Ririn; Ari Sunandar; Hanum Mukti Rahayu (Bioedukasi Jurnal Pendidikan Biologi, 2025)
One of the main obstacles in the teaching and learning process at MA Darul Ulum is the low student interest in learning due to the use of conventional and abstract media, such as textbooks. This study aims to determine the validity and student responses toward learning media developed using the Prezi application with an elaboration approach. The research employed a Research and Development (R&D) design based on the 4D model, which consists of four stages: define, design, develop, and disseminate. Data analysis was conducted descriptively based on expert validation and student response questionnaires. The results of the media validation showed scores of 87.96% from media experts, 85% from material experts, and 91.67% from language experts, all of which fall into the “very validâ€ category. Field test results indicated that the elaboration-based Prezi media effectively enhanced students’ learning outcomes. Student response questionnaires obtained percentages of 91.91% in the small-scale trial and 89.89% in the large-scale trial, both categorized as “very good.â€ Based on these findings, the elaboration-based Prezi media is considered valid, practical, and effective for use in teaching the human respiratory system topic in senior high school biology.